A Functional Typology Perspective on Exclamative Sentences in Sundanese Folktales - Wida Mulyanti; Eri Kurniawan; Rinaldi Supriadi (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2025)
This study analyzes exclamatory constructions in Sundanese folktales (narrative genre), 9,005 tokens from 30 texts through corpus-driven and functional-typological frameworks. Findings reveal that directive particles (hayu), intensifiers (pisan, teuing), and interjections (duh, yeuh)—not generic emotional terms—dominate exclamatory usage, reflecting communal pragmatics. The particle hayu (7 instances), as in “Hayu urang buru embe!” (“Let’s chase the goat!”), merges mobilization with collective urgency through syntactic patterns: direct action, metaphorical appeals (“paganteng-ganteng tunangan!” = “most handsome fiancés!”), and elliptical structures. Intensifiers like pisan (29 instances) amplify affective states (“Haus pisan!” = “So thirsty!”), while reduplication (alus-alus teuing = “so beautiful!”) heightens emotive emphasis. Interjections (duh, yeuh) anchor climactic moments through performative incompleteness (“Duh, Gusti...” = “Oh, God…”). Hybrid interrogative-exclamatives (“Naha anjeun teu éra...?!” = “How dare you?!”) and imperative-exclamatives (“Kudu make akal!” = “Use your brain!”) blur grammatical boundaries, prioritizing cultural intent over syntax. These constructions challenge Eurocentric mood models, instead encoding communal ethics, moral critique, and oral tradition aesthetics. The study underscores exclamatives as cultural-linguistic acts vital to sustaining Sundanese narrative identity, advocating context-sensitive approaches in indigenous language pedagogy and folklore preservation.